Announcement: 2022 Brendan Walsh Prize (The Economic and Social Review, 2022)
Announcement: 2022 Brendan Walsh Prize: The 2022 Brendan Walsh Prize has been awarded to Brian Nolan (University of Oxford) and Bertrand Maître (Economic and Social Research Institute) for their paper “Does Household Worklessness Explain Ireland’s High Working-Age Market Income Inequality?” The Brendan Walsh Prize was inaugurated in 2018 to select the best paper published in The Economic and Social Review in the previous year. The prize includes €1,000 and a certificate. The selection was made by the following sub-committee of the Economic and Social Studies Council: Adele Bergin (Economic and Social Research Institute), Micheál Collins (University College Dublin), John Cullinan (NUI Galway), Aedín Doris (Maynooth University), and Yvonne McCarthy (Central Bank of Ireland).